USE OF BULGARIAN LEVA BANKNOTES OVER A QUARTER CENTURY, EXPERT ASSESSMENT AND CITIZENS’ TRUST IN DIFFERENT INSTITUTIONS - Ruseva, Nevena; Georgiev, Georgi; Kisyova, Katina (E-Journal VFU, 2025)
The article examines the relationship between the long-term use of the Bulgarian lev (the last 25 years of emissions after 1999) and citizens' trust in institutions that have the authority and expert capacity to recognize genuine and counterfeit banknotes. An empirical study was conducted in the period 22.08.2025 - 11.09.2025 among 371 respondents. In a historical and normative context, the study also highlights a practical paradox: forensic experts from the Ministry of Interior routinely examine complex protected documents with printing and security techniques identical to banknotes, but by virtue of the current distribution of competencies they are not allowed to prepare expert opinions on the authenticity of banknotes. This leads to incomplete use of the available expert potential and to weaker public recognition of the Ministry of Interior as a source of security.
Keywords: expertise; forensics; law; security; currency examination